Structure of the E. coli agmatinase, SPEB. - Iva Chitrakar; Syed Fardin Ahmed; Andrew T Torelli; Jarrod B French (PLoS ONE, 2021)
Agmatine amidinohydrolase, or agmatinase, catalyzes the conversion of agmatine to putrescine and urea. This enzyme is found broadly across kingdoms of life and plays a critical role in polyamine biosynthesis and the regulation of agmatine concentrations. Here we describe the high-resolution X-ray crystal structure of the E. coli agmatinase, SPEB. The data showed a relatively high degree of pseudomerohedral twinning, was ultimately indexed in the P31 space group and led to a final model with eighteen chains, corresponding to three full hexamers in the asymmetric unit. There was a solvent content of 38.5% and refined R/Rfree values of 0.166/0.216. The protein has the conserved fold characteristic of the agmatine ureohydrolase family and displayed a high degree of structural similarity among individual protomers. Two distinct peaks of electron density were observed in the active site of most of the eighteen chains of SPEB. As the activity of this protein is known to be dependent upon manganese and the fold is similar to other dinuclear metallohydrolases, these peaks were modeled as manganese ions. The orientation of the conserved active site residues, in particular those amino acids that participate in binding the metal ions and a pair of acidic residues (D153 and E274 in SPEB) that play a role in catalysis, are similar to other agmatinase and arginase enzymes and is consistent with a hydrolytic mechanism that proceeds via a metal-activated hydroxide ion.